Difficulties in Conducting Long Term Follow Ups in Psychotherapy Research—Issues in the Literature and Data From a Randomized Therapy Comparison Study for Posttraumatic Stress Disorder. Issue 7 (July 2018) - König, Julia; Karl, Regina; Rosner, Rita; Butollo, Willi
Abstract : Abstract: Studies of psychotherapy for posttraumatic stress disorder (PTSD) typically encompass short follow-up periods, leading to a dearth of information on the long-term course of symptoms after treatment. We summarize existing long-term follow-up studies and highlight the issues making such research difficult. In this context, we report on a 2-year follow-up on a randomized treatment study comparing dialogical exposure therapy and cognitive processing therapy for adults with PTSD after type I trauma. Many of the problems connected to long-term follow-up also pertained to this study. Attrition was high, and the recruited sample was not representative of the study completers. Gains made during therapy were mostly stable, with no significant differences between interventions. At least for an originally successful subset of patients, the gains made during both treatments in our study tended to stay stable 2 years after the end of treatment.